Integration of Automatic Identification and Data Capture devices with SAP R/3 - Hafiz Abd Rahman, Nazrul Aminur (Universiti Teknologi Petronas, 2006)
Although SAP R/3 has become widely utilized as a means to change IT systems and business processes, not all organizations embarking on its implementation have achieved their intended results particularly in inventory management. Automatic identification and data capture are distinguished as an important emergent area of enterprise resource planning (ERP) implementation. Due to optimization and globalization of business operation, efficient supply chain management becomes more crucial. The objective of this project is to present the accessibility of barcode technology in providing automated data handling. A number of products are available for implementation, but this project focuses on SAP R/3 from SAP AG. Business scenario from media industries are been utilized to stimulate the real environment of barcode implementation within SAP system. Configuration of the SAP system is implemented to obtain the optimal solutions based on requirement gathered from the first phase of the project. Replication of the case study illustrates the applicability of the approach to overcome the issues and the advantages of the solution. Simulation of the result is expected to be a key answer for reducing the human errors occurs in business process transaction and increase the employee's productivity.